Changes in university educational technologies applied in business education and management based on stakeholder theory - Iershova, N. Yu.; Portna, O. V.; Khoroshylova, Yu. (ELIT – Ekonomska laboratorija za istraživanje tranzicije, Podgorica, Crna Gora, 2020)
At the present stage of societal evolution there is a rapid development of innovation processes observed in university education. Indeed, the standards of higher education are getting higher and being determined under the influence of stakeholders and global processes of redistribution in the labour market. The main vectors of development in Ukraine’s higher education are outlined in Decree of the President of Ukraine of September 14, 2000. (No. 1072-2000): On the Program of Ukraine’s Integration into the European Union, Orders of the Cabinet of Ministers of Ukraine, Decisions of the Ministry of Education and Science of Ukraine. The main task facing university education in the field of business education and management based on the theory of stakeholders is to ensure the potential development for future professionals in accordance with the needs of stakeholders. In addition, many state agencies, banks, companies do not simply need specialists but economists, managers, financiers, and problem-solving professionals. Therefore, the system of higher education requires changes in approaches to organizing the educational process. The creation of a single educational space, the introduction of a degree system of higher education (as provided by the Law of Ukraine “On Higher Education”), the transition to educational and professional standards taking into account the interests of stakeholders necessitate reorientation of the pedagogical process to implement new approaches into education.
Keywords: management; stakeholder; university educational technologies; business education; economy